2014
DOI: 10.1016/j.enpol.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Does EU emissions trading bite? An event study

Abstract: The aim of this paper is to examine whether shareholders consider the EU Emissions Trading Scheme (EU ETS) as value-relevant for the participating firms. An analysis is conducted of the share prices changes as caused by the first publication of compliance data in April, 2006, which disclosed an over-allocation of emission allowances. Through an event study, it is shown that share prices actually increased as a result of the allowance price drop when firms have a lower carbon-intensity of production and larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…These studies include Bushnell et al (2013) and Jong et al (2014). They find that the drastic drop in carbon prices over a three-day window had a negative impact on the stock returns of carbon-intensive firms.…”
Section: Literature Reviewmentioning
confidence: 96%
“…These studies include Bushnell et al (2013) and Jong et al (2014). They find that the drastic drop in carbon prices over a three-day window had a negative impact on the stock returns of carbon-intensive firms.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Oestreich and Tsiakas [11] found that on average, firms that received free carbon emission allowances under the EU ETS significantly outperformed firms that did not, as measured by German stock returns. There was no significant value impact from firms' allowance trading activity or from the pass-through of carbon-related production costs (carbon leakage) [12]. While firms reduced their environmental costs, stock prices also fell for firms in both carbon-and electricity-intensive industries within the EU when the EU CO 2 allowance price dropped 50 per cent in late April 2006 [13].…”
Section: Carbon Allowance Allocation Based On Efficiencymentioning
confidence: 91%
“…If companies face direct costs for every ton of CO 2 they emit, they will take these emissions into account in everyday decision making. Jong et al (2014) have found evidence that this is not only the case for managers who are confronted with the cost of carbon emissions immediately, but also for investors on stock markets. By correlating allowance prices with companies' share prices they demonstrate that the EU ETS does 'bite', i.e.…”
Section: Impact Beyond Project Scopementioning
confidence: 99%
“…In order to cover also the more specific aspects of our analysis, this was complemented with parameterized snowballing from three additional reference points: innovation (Borghesi et al 2015;Schmidt et al 2012;Kemp and Pontoglio 2011), investments (Jong, Couwenberg, and Woerdman 2014;Löfgren et al 2013;Grubb 2012), institutions (Voß and Simons 2014;Hildén 2014;LaBelle 2012), and integration (Lehmann and Gawel 2013;Schlomann and Eichhammer 2014;Gawel, Strunz, and Lehmann 2014).…”
Section: Methodology and Materialsmentioning
confidence: 99%